Competency building in a busy working day for librarians and for libraries (Journal of EAHIL, 2023)
Medical librarians know very well that they must build new competencies to offer relevant services and develop new library services. In a workshop at the EAHIL conference 2023, suggestions for competency building, and how libraries can build competency, were discussed. Positive and enthusiastic participants came up with many ideas: different types of clubs, webinars and courses, knowledge sharing with colleagues, regularly block out time, or just solve your tasks in a new way. The experiences showed that competency building in a busy work schedule is possible. The initiatives have in common that they portray an attitude to learn more, but also the willingness to organise activities and share competency with colleagues.